Effects of corticosteroids and hyaluronic acid on torn rotator cuff tendons in vitro and in rats. Issue 10 (20th July 2015) - Nakamura, Hidehiro; Gotoh, Masafumi; Kanazawa, Tomonoshin; Ohta, Keisuke; Nakamura, Keiichirou; Honda, Hirokazu; Ohzono, Hiroki; Shimokobe, Hisao; Mitsui, Yasuhiro; Shirachi, Isao; Okawa, Takahiro; Higuchi, Fujio; et al.
ABSTRACT Corticosteroids (CS) or hyaluronic acid (HA) is used in subacromial injection for the conservative treatment of rotator cuff tears (RCT); this study addresses the question of how CS and HA affect the tendon tissue and fibroblasts in vitro and in rats. Cell proliferation assays were performed in human tendon fibroblasts from RCT. Rats underwent surgery to create RCT, and the surgical sites were injected with CS or HA. The rotator cuff tendons were subjected to biomechanical testing, microscopic and immunohistochemical analysis of proliferating cell nuclear antigen (PCNA), and ultrastructural analysis. Cell proliferation was significantly decreased with CS in vitro (p < 0.05). Maximal load of CS‐treated tendons was significantly decreased compared with that of HA‐treated tendons (p < 0.05), as well as PCNA+ cells at 2 weeks (p < 0.05). Ultrastructural observations of the CS‐treated rats detected apoptosis of tendon fibroblasts 24 h after surgery. Histological and biomechanical data 4 weeks after surgery were not significant among the three groups. Unlike HA, CS caused cell death, and inhibition of the proliferation of tendon fibroblasts, leading to a delay of tendon healing involved and a subsequent decrease of biomechanical strength at the surgical site. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1523–1530, 2015.